Unusual formation of nano-particles of CdO and Cd(OH)(2) from the reaction of dimethyl cadmium with DMF - Singh, Narendra; Charan, Shobhit; Patil, K. R.; Viswanath, A. K.; Khanna, P. K. (Materials Letters, 2006)
This paper presents generation of CdO and Cd(OH)(2) nano-particles from Dimethyl Cadmium in DMF. The CdO nano-particles were obtained instead of CdSe, even when the reaction was done in presence of 1,2,3-selenadiazole (the source of selenium) with Me2Cd in DMF (product-I). The direct reaction of Me2Cd in DMF also leads to formation of CdO (product-II). However, Cd(OH)(2) nano-particles were obtained when Me2Cd was refluxed in DMF for a few hours followed by reaction of H2S gas (product-III). The formation of Cd(OH)(2) was also established via decomposition Of Me2Cd:Et2O adduct (product-IV). Nano-particles of CdO and Cd(OH)(2) (product-I to product-IV) were characterized by X-ray powder diffraction (XRD), TEM and SEM/EDS measurements, FTIR, thermal analysis (TGA) and XPS analysis. The particle size of all the products as calculated by XRD patterns were in the range of about 20 nm. TEM images showed that the products are agglomerated clusters with the particles in the nano-meter regime. The synthesis however, is understood to be unusual as the reactions with selenium source and sulfur source should have generated the CdSe and CdS however, the end products were always found to be the product-I to product-IV (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Nanoparticles; Semiconductor; XRD

Use of poly(o-toluidine)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel - Chaudhari, Sudeshna; Patil, P. P.; Mandale, A. B.; Patil, K. R.; Sainkar, S. R. (Journal of Applied Polymer Science, 2007)
This study explored the possibility of using poly(o-toluidine) (POT)/ZrO2 nanocomposite coatings for the corrosion protection of mild steel in a chloride environment. POT/ZrO2 nanocomposite coatings were synthesized on steel substrates through an electrochemical route. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, and X-ray photoelectron spectroscopy. The performance of POT/ZrO2 nanocomposites as protective coatings against the corrosion of mild steel in aqueous 3 wt % NaCl was evaluated with the potentiodynamic polarization technique and electrochemical impedance spectroscopy. The results of this study demonstrate that POT/ZrO2 nanocomposite coatings provide better protection for mild steel against corrosion than pure POT coatings. The corrosion potential was about 0.312 V versus a saturated calomel electrode, more positive in aqueous 3 wt % NaCl for the nanocomposite-coated steel than the uncoated steel, and the corrosion rate of steel was reduced by a factor of almost 51. (c) 2007 Wiley Periodicals, Inc.
Keywords: Coatings; conjugated polymers; FTIR; Nanocomposites; synthesis